Soil methane emissions from plain poplar (Populus spp.) plantations with contrasting soil textures - Xuehong Ma; Huili Feng; Jiahuan Guo; Changhui Peng; Daniel Kneeshaw; Weifeng Wang (Scientific Reports, 2024)
Abstract The forest soil methane (CH4) flux exhibits high spatiotemporal variability. Understanding these variations and their driving factors is crucial for accurately assessing the forest CH4 budget. In this study, we monitored the diurnal and seasonal variations in soil CH4 fluxes in two poplar (Populus spp.) plantations (Sihong and Dongtai) with different soil textures using the static chamber-based method. The results showed that the annual average soil CH4 flux in the Sihong and Dongtai poplar plantations was 4.27 ± 1.37 kg CH4-C ha–1 yr–1 and 1.92 ± 1.07 kg CH4-C ha–1 yr–1, respectively. Both plantations exhibited net CH4 emissions during the growing season, with only weak CH4 absorption (–0.01 to –0.007 mg m–2 h–1) during the non-growing season. Notably, there was a significant difference in soil CH4 flux between the clay loam of the Sihong poplar plantation and the sandy loam of the Dongtai poplar plantation. From August to December 2019 and from July to August and November 2020, the soil CH4 flux in the Sihong poplar plantation was significantly higher than in the Dongtai poplar plantation. Moreover, the soil CH4 flux significantly increased with rising soil temperature and soil water content. Diurnally, the soil CH4 flux followed a unimodal variation pattern at different growing stages of poplars, with peaks occurring at noon and in the afternoon. However, the soil CH4 flux did not exhibit a consistent seasonal pattern across different years, likely due to substantial variations in precipitation and soil water content. Overall, our study emphasizes the need for a comprehensive understanding of the spatiotemporal variations in forest soil CH4 flux with different soil textures. This understanding is vital for developing reasonable forest management strategies and reducing uncertainties in the global CH4 budget.